2018
DOI: 10.3390/healthcare6030079
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Healthcare System in Japan

Abstract: This paper describes the present Japanese oral healthcare system and outlines the future challenges and perspectives for Japan. Japan has developed a system for providing high-quality and appropriate health care efficiently through a universal health insurance system which has been in operation since 1961. This health insurance covers most restorative, prosthetic and oral surgery treatment. Therefore, all people can receive dental treatment at a relatively low cost, with the same fees applying throughout the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 3 publications
0
72
0
16
Order By: Relevance
“…Japan is the country with the lowest out‐of‐pocket dental expenditures because the public insurance system covers a wide range of dental services, and it is also ranked as the country with the highest access to dental care, with 3.2 dental visits per person per year in 2015. Additionally, Japan has adopted a universal health care insurance system for the general population since 1961, through which beneficiaries can access medical and dental treatment when needed and only pay 10%–30% of the total costs of treatment depending on income, age and health condition. Nevertheless, dental implant therapy is not covered by insurance except in rare cases of absolute necessity, such as those involving congenital, pathological and accidental jaw bone deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Japan is the country with the lowest out‐of‐pocket dental expenditures because the public insurance system covers a wide range of dental services, and it is also ranked as the country with the highest access to dental care, with 3.2 dental visits per person per year in 2015. Additionally, Japan has adopted a universal health care insurance system for the general population since 1961, through which beneficiaries can access medical and dental treatment when needed and only pay 10%–30% of the total costs of treatment depending on income, age and health condition. Nevertheless, dental implant therapy is not covered by insurance except in rare cases of absolute necessity, such as those involving congenital, pathological and accidental jaw bone deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…showed that the increased number of teeth in the oral cavity was associated with an increased number of microorganisms in the saliva of older people residing in long‐term care facilities . Indeed, the number of present teeth in older individuals in Japan has substantially increased within the most recent 20 years, as reported by Zaitsu et al . Furthermore, Takahashi et al .…”
Section: Introductionmentioning
confidence: 76%
“…Regarding additional risk factors for aspiration pneumonia in modern Japan, Tohara et al showed that the increased number of teeth in the oral cavity was associated with an increased number of microorganisms in the saliva of older people residing in long-term care facilities. 8 Indeed, the number of present teeth in older individuals in Japan has substantially increased within the most recent 20 years, as reported by Zaitsu et al 9 Furthermore, Takahashi et al reported that subclinical aspiration of saliva occurred in institutionalized patients who experienced recurrent pneumonia; therefore, the increased number of present teeth can be a risk factor for aspiration pneumonia, even under standardized daily oral care conditions. 10 In addition, some studies have shown that professional oral care can significantly reduce the onset of AVRI among older people, as indicated for pneumonia.…”
Section: Introductionmentioning
confidence: 89%
“…A systematic review and meta‐analysis on access to dental care including 7 395 697 participants from 28 countries showed that dental utilization was higher among countries with a higher human developmental index (HDI) . Japan is a country with a high HDI and has the highest dental utilization, with wide dental care coverage provided by universal health insurance . However, there still exist income inequalities in access to dental care .…”
Section: Discussionmentioning
confidence: 99%
“…Japan's public healthcare insurance covers a wide range of dental treatments . Japan achieved universal health insurance in 1961, which contributed to population health outcome such as longevity and boosted social stability and equity .…”
Section: Introductionmentioning
confidence: 99%